2006
DOI: 10.1007/s00239-005-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of BK Virus Based on Complete Genome Data

Abstract: The human polyomavirus BK virus (BKV) is ubiquitous in humans, infecting children asymptomatically. BKV is the only primate polyomavirus that has subtypes (I-IV) distinguishable by immunological reactivity. Nucleotide (nt) variations in a major capsid protein (VP1) gene region (designated the epitope region), probably responsible for antigenic diversity, have been used to classify BKV isolates into subtypes. Here, with all the protein-encoding gene sequences, we attempted to elucidate the evolutionary relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 62 publications
3
57
0
4
Order By: Relevance
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings raise the interesting question of whether different BKV genotypes or subgenotypes exhibit altered tissue tropism or different levels of virulence in vivo. Although previous studies have surveyed BKV genotypes found in nephropathic lesions (15,16,(37)(38)(39), these studies have relied on BKV-I-biased PCR primers that underestimate the abundance of BKV genotypes II, III, and IV (40). The possibility that commonly used PCR primers do not robustly detect non-genotype I BKVs (particularly in the case of individuals coinfected with multiple BKV genotypes) is consistent with our observation that BKV-II seroprevalence (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Based on initial phylogenetic analyses, we chose BKV representatives from each of the major branches of the tree, specifically BKV-Ia (isolate name BK-D; accession number JF894228), BKV-Ib1 (KOM-5; AB211374) (15), BKV-Ib2 (PittVR2; DQ989796) (16), BKV-Ic (RYU-2; AB211377) (15), BKV-II (GBR-12; AB263920) (17), BKV-III (KOM-3; AB211386) (15), BKV-IVb1 (THK-8; AB211390) (15), and BKV-IVc2 (A-66H; AB369093) (2,9). A codonmodified version of the VP1 gene of each variant was designed according to a previously reported algorithm (18), with the exception of variant KOM-5, which was expressed from an unmodified late region fragment that includes the native agnoprotein and VP2/3 genes (19).…”
Section: Methodsmentioning
confidence: 99%
“…The sequences of the primer-probe sets used in this assay are nearly identical to those of BKPyV and JCPyV from Japan (16,23). The most commonly used strains outside Japan are Dunlop for BKPyV and Mad1 for JCPyV.…”
Section: Discussionmentioning
confidence: 99%
“…2). The geographic origins of reference isolates were the United States (DUN), Kenya (KEN-1), South Africa (WW), Ethiopia (ETH-3), The Netherlands (Dik and JL), Finland (FNL-12), the United Kingdom (AS and GBR-12), and Japan (KOM-2, KOM-3, MT, RYU-2, RYU-3, THK-8, TW-1, and TW-3) (13,16,20,25 (Fig. 1).…”
mentioning
confidence: 99%